Estudos baseados em uma única campanha de amostragem podem produzir resultados robustos para o monitoramento da qualidade da água? Um estudo de caso no reservatório de Itupararanga, SP, Brasil - Beghelli, Frederico Guilherme de Souza [UNESP]; Pompêo, Marcelo Luiz Martins; Páscoli, Mônica; Lira, Vivian Silva [UNESP]; de Lima, Renata; Moschini-Carlos, Viviane [UNESP] (FapUNIFESP (SciELO), 2016)
Aim: The aim of this study was to conduct a rapid and comprehensive analysis of the reservoir using physical, chemical and biological variables comprising water and sediment as also to verify if a one-sampling campaign can produce information that is robust enough for monitoring purposes. Methods: One-sampling campaign was performed along the central body of Itupararanga reservoir comprising five sampling points. The following physico-chemical and biological variables were measured in each of them from water samples: temperature, pH, concentration of dissolved oxygen, electric conductivity, suspended matter, total nitrogen and phosphorus and fecal coliforms. A genotoxicity assay with Allium cepa was also performed with water from each one of the five sampling points. As a complement, the phytoplankton and benthic macroinvertebrates communities were also analyzed in the two most distant sampling points (P1 and P5). Results: Results indicate a scenario with eutrophication and toxicity. High concentrations of fecal coliforms were recorded and there is a worrying prevalence of cyanobacteria - potential toxin producers - in phytoplankton community. Benthic macroinvertebrates analysis suggests poor quality of the water and sediments. Genotoxicity tests suggest the presence of toxic substances along the waterbody. Conclusions: It is concluded that Itupararanga reservoir has water with poor quality that could be related to the land uses around the reservoir. The comprehensive approach performed here - where distinct sources of monitoring variables was considered - despite the rapid protocol (one campaign), was enough to respond to the distinct anthropic impacts received by the reservoir. Considering it, this approach is recommended as a rapid diagnostic tool.
Can a one-sampling campaign produce robust results for water quality monitoring? A case of study in itupararanga reservoir, SP, Brazil
Keywords: Bioindicator; Biomonitoring; Hepatotoxins; Neurotoxins; Water quality monitoring